Sprouting and rooting response of white mulberry (Morus alba Unn.) to pre-conditioning and chemical treatments - Thakur, I.K. (Indian Journal of Agroforestry, 2020)
The techniques for the effective vegetative propagation of white mulberry, an important agro forestry tree species, were developed specially for those clones or genotypes which are difficult or moderate to root. The study investigated the influence of pre-conditioning (girdling) and chemical treatments (auxin) with co-factor, sucrose and fungicide (0.2% p-HBA+2% sucrose + 5% captan) on sprouting and rooting characteristics of branch cuttings during spring (February - March) and rainy (July-August) seasons. Sprouting and rooting were better in girdled propagules than non-girdled. Sprouting, rooting and root number were better in cuttings set in spring as compared to rainy season. Treatment of girdled cuttings with chemical formulations of 0.2% IBA+O.2% p-HBA+2% sucrose +5% captan maximized sprouting (100%) and rooting (98.22%) with more root number (16.02%), ensuring better survival, in spring season whereas, mean sprout length (16.23 cm) and root length (12.87 cm) were greatest with 0.3% IBA + 0.2% HBA+2% sucrose+5% captan.